Explaining Positional Differences of Performance Profiles for the Elite Female Basketball Players - Zhai, Zongpeng; Guo, Yongbo; Zhang, Shaoliang; Li, Yuanchang; Liu, Hongyou (Frontiers in Psychology, 2021)
The aim of the present study was to explore the differences in technical performances of players considering playing positions by controlling the effect of situational variables in each FIBA female continental basketball competitions. Samples of 9208 observations from 471 games in the America, Africa, Asia and Europe Championships during 2013-2017 were collected and analyzed by generalized mixed linear modeling. The results showed that Centers from Europe had more 2-point made (ES = 0.69), 2-point attempted (ES = 0.79), and offensive (ES = 0.64) & defensive (ES = 0.48) rebounds than forwards. Asian and European guards performed a fewer number of 2-point made (ES = 0.90; 0.91), 2-point attempted (ES = 1.06; 0.98), and offensive (ES = 1.30; 1.23) & defensive (ES = 0.93; 0.94) rebounds than Asian and European centers. African and Asian forwards had more 2-point made (ES = 0.48; 0.50), 2-point attempted (ES = 0.50; 0.56) than guards. This study helps to better understand the technical demands of female basketball among different international competitions, which could pave a new way to analyze the development trend of female basketball and promoting specific training plans and game strategies for coaches and players.